Post-translational Modifications of the Protein Termini - Chen, Li; Kashina, Anna (Frontiers in Cell and Developmental Biology, 2021)
Post-translational modifications (PTM) involve enzyme-mediated covalent addition of functional groups to proteins during or after synthesis. These modifications greatly increase biological complexity and are responsible for orders of magnitude change between the variety of proteins encoded in the genome and the variety of their biological functions. Many of these modifications occur at the protein termini, which contain reactive amino- and carboxy-groups of the polypeptide chain and often are pre-primed through the actions of cellular machinery to expose highly reactive residues. Such modifications have been known for decades, but only a few of them have been functionally characterized. The vast majority of eukaryotic proteins are N- and C-terminally modified by acetylation, arginylation, tyrosination, lipidation, and many others. Post-translational modifications of the protein termini have been linked to different normal and disease processes and constitute a rapidly emerging area of biological regulation. Here we highlight recent progress in our understanding of post-translational modifications of the protein termini and outline the role that these modifications play in cellular processes.